Mulieris dignitatem in božja previdnost - Jogan, Maca (Družboslovne razprave, 2013)
The author addresses the key characteristics of the religious shaping of women's identity and their social role in the Catholic Church (CC), with the following aims: to disclose the misogyny contained in relevant CC explanations, to evaluate its reaction to the social processes of emancipationand to answer the question of whether Catholic feminism means a radical break in managing the "second sex". On the basis of a content analysisof post-council official documents, she concludes that the key misogynist and androcentric characteristic of the explanations remains. Otherwise, the CC deals with topics of greater gender equality, although it strongly rejects those approaches which include necessary structural changes and defends the "new", "Catholic feminism", albeit according to its reductionist concept of woman as a subordinated assistant to man. The CC itself remains a strongly male-dominated institution, even though during the last few decades broader social opportunities for women's autonomy have increased and this has also decreased the coercion of "God's plan" regarding the managing of women.
Keywords: Androcentrism; Catholic Church; Katoliška cerkev; Moškosrediščnost; Catholicism; Feminism; Katolicizem; Women; Feminizem; Dignity; Ženske; woman; Dostojanstvo; družbena vloga; spolna diskriminacija